(untitled) (JURNAL IBU DAN ANAK, 2020)
Abstract Low birth weight (LBW) is closely related to infant mortality and morbidity. The LBW would be at risk of still birth, growth and development retardation. Besides that, individuals with a history of LBW have a high risk factor for the incidents of hypertension, heart disease and diabetes after reaching the age of 40 years (Kosim MS in Mahayana, 2012). The purpose of this study is to determine the factors that influence the incident of LBW in Regional General Hospital of Arifin Achmad, Pekanbaru 2018. This research was an analytic using a cross-sectional research design,. The data were taken from medical record. The population in this study were all of maternal women whose babies were treated in the perinatology room of Regional General Hospital of Arifin Achmad, Pekanbaru. The total of population and sample are 328 and 250 respectively. The results show that: there is no significant relationship between maternal age and LBW incident 0.990 (p-value> 0.05), no correlation between parity and LBW incident with p value = 0.661 (p value>α), there is no significant relationship between the illness of mother during pregnancy with LBW incident with p value = 0.773 (p value>α), no significant relationship between placental abnormalities during pregnancy and incident of LBW with p value = 0.153 (p value>α) , there is a significant relationship between pregnancy age and LBW incident with p value = 0.000 (p value ≤ α), and there is a significant relationship between twin pregnancy and incident of LBW with p value = 0.002 (p value>α). From this research, it can be suggested that the community, especially pregnant women and their families to increase much more information on maternal and child health through social media, to attend counseling and seminars, and to ask the medical personnels directly to the nearest health facilities about LBW. By these suggestions LBW hopefully could be avoided. Keyword : Low Birth Weight (LBW)